Functional Study of Novel Bartter’s Syndrome Mutations in ClC-Kb and Rescue by the Accessory Subunit Barttin Toward Personalized Medicine - Sahbani, Dalila; Strumbo, Bice; Tedeschi, Silvana; Conte, Elena; Camerino, Giulia Maria; Benetti, Elisa; Montini, Giovanni; Aceto, Gabriella; Procino, Giuseppe; Imbrici, Paola; Liantonio, Antonella (Frontiers in Pharmacology, 2020)
Type III and IV Bartter syndromes (BS) are rare kidney tubulopathies caused by loss-of-function mutations in the CLCNKB and BSND genes coding respectively for the ClC-Kb chloride channels and accessory subunit barttin. ClC-K channels are expressed in the Henle’s loop, distal convoluted tubule, and cortical collecting ducts of the kidney and contribute to chloride absorption and urine concentration. In our Italian cohort, we identified two new mutations in CLCNKB, G167V and G289R, in children affected by BS and previously reported genetic variants, A242E, a chimeric gene and the deletion of the whole CLCNKB. All the patients had hypokalemia and metabolic alkalosis, increased serum renin and aldosterone levels and were treated with a symptomatic therapy. In order to define the molecular mechanisms responsible for BS, we co-expressed ClC-Kb wild type and channels with point mutations with barttin in HEK 293 cells and characterized chloride currents through the patch-clamp technique. In addition, we attempted to revert the functional defect caused by BS mutations through barttin overexpression. G167V and A242E channels showed a drastic current reduction compared to wild type, likely suggesting compromised expression of mutant channels at the plasma membrane. Conversely, G289R channel was similar to wild type raising the doubt that an additional mutation in another gene or other mechanisms could account for the clinical phenotype. Interestingly, increasing ClC-K/barttin ratio augmented G167V and A242E mutants’ chloride current amplitudes towards wild type levels. These results confirm a genotype-phenotype correlation in BS and represent a preliminary proof of concept that molecules functioning as molecular chaperones can restore channel function in expression-defective ClC-Kb mutants.